Dimerization of 3-Chlorooxindoles Mediated by Potassium Ethylxanthate: Synthesis of Isoindigos - Meesin, Jatuporn; Chotsaeng, Nawasit; Kuhakarn, Chutima (Synlett, 2022)
A novel dimerization of 3-chlorooxindoles promoted by potassium ethylxanthate to access isoindigo derivatives is described. The reactions proceeded readily at room temperature in short reaction times. A mechanistic study revealed that the 3-chlorooxindole is initially converted into O-ethyl S-(2-oxo-2,3-dihydro-1H-indol-3-yl) dithiocarbonate, which subsequently undergoes dimerization with elimination of carbon disulfide. In almost all cases, analytically pure isoindigos were isolated in moderate to good yields without a requirement for chromatographic purification.
Keywords: isoindigos; potassium ethylxanthate; dimerization; chlorooxindoles; carbon disulfide